PFD with improved average gain and minimal blind zone combined with lock-in detection for fast settling PLLs. (October 2021) - H.K., Ravi; Mukherjee, Jayanta
Abstract: In this paper, two Phase frequency detector (PFD) architectures and a PFD with lock-in detection (PFD-LID) are proposed that are designed using the new techniques for selectively resetting the outputs to achieve improved average gain with a lower blind zone. The two proposed PFDs are designed and fabricated using 180 nm CMOS process. The circuits are tested with the variations in the supply voltage from 1.3 V to 1.8 V, achieving higher average gain and the measured blind zone of 3 ps, which is around five times less than earlier reported works. Also, the proposed selective reset techniques are used to design the PFD-LID. Both the PFDs and PFD-LID are validated using the traditional phase-locked loop (PLL) architecture by achieving minimal settling time of the PLL.